Responses to Sarcasm in Three Star Trek Movies - Shafira Sherin; Adi Sutrisno (Universitas Gadjah Mada, 2019)
Sarcasm has been widely studied in various disciplines such as linguistics, psychology, neurology, sociology, and even cross-cultural studies. Its aggravating nature, however, often elicits various responses by the hearer. This study attempts to investigate responses to sarcasm by the characters of three Star Trek “reboot” version movies. It aims to examine responses to sarcasm and to analyze the patterns of responses to sarcastic remarks in relation to the characters’ interpersonal relationship. The data used in this research were taken from the dialogues of the movies, which were categorized into eight classes of responses: laughter, literal, zero response, smile, nonverbal, sarcasm, topic change, and metalinguistic comment. The results show that the most frequent responses conveyed by the characters were literal responses (29.41%), whereas the least frequent responses are laughter (1.96%). There is no pattern in responding to sarcastic remarks in relation to the interpersonal relationship between the interlocutors. However, strangers tend to respond in literal, zero response, and topic change. Meanwhile, close acquaintance tend to give various responses.Keywords: interpersonal relationship; pragmatics; response; sarcasm.